Map of central Alaska, Cook Inlet and Copper River, including Klondike, White, Tanana and Minook Rivers / by J.B. Tyrrell, 1898 - Tyrrell, Joseph Burr, 1858-1957; (Washington, D.C. : U.S.C. & G Survey, U.S. Geol. Survey; Washington, D.C. : The Norris Peters Co., Photo-litho;, 1898)
Shows trails, general areas of mineral resources, magnetic variations, northern limit of glaciation, etc.; Relief shown by hachures and spot heights. Depths shown by isolines.; Includes distance charts, 2 inset maps and notes.; Insets: Map of Juneau to Miles Canyon -- Key map of Alaska Grayscale; 1:1,900,800